Students during the first six weeks of the 1934-35 Spring quarter. - Unknown:::Creator::::::::::::
Written on verso: "1st 6 weeks Spring Quarter 1934-1935; Betty Philhot, Marguerite Cooher, Quez Fetzer, F. Conkey (faculty), Margaret Conneau."